Creating Girls Casual Wear Designs Influenced By the Characteristics of Japanese Street Fashion Style - Amany el said Eldosuky (Journal of Architecture, Art & Humanistic Science, 2023)
Clothes are a symbol of the culture of each country and a part of its heritage, it should be noted that the study of peoples' clothing cultures achieves richness in the field of fashion design and helps to develop new design lines, as the innovative process is the discovery of what is new, whether in the form of ideas, shapes, symbols or re organizing things that already exist in a new form or adding a new factor to an already existing system or thing. this research focuses on studying and analyzing the characteristics of Japanese street fashion, street style fashion referred to fashion styles that were created by general public instead of professional fashion designers where people have mixed their own styles by using several fashion elements in order to identify themselves, street fashions could come from any person regardless of class statuses, street fashion trend continued to spread widely across Japan where rapid adoption by youth has led to the occurrence of fashion identities in each district of Tokyo, Japanese street fashion also caught worldwide attention and inspired global trend, therefore the research analyzed the characteristics of Japanese street style including its design lines, different types of fabrics, contrasting cuts, distinctive colors and many details which making it a rich source for innovative designs, the Japanese street fashion impact on global fashion has been highlighted by presenting some international fashion designers collections which affected by this trend, where the research included how to take advantage of the distinctive characteristics of street fashion in Japan in creating casual designs that suit the Egyptian girl, as seven innovative designs influenced by this trend were implemented in a way that suits girls in the Egyptian society in the age group of 18-30 years.